Cooperative Adaptive Cruise Control System for Autonomous Vehicles with Linear Quadratic Optimal Regulator and Feedforward Control Method - Adiguzel, Fatih (GAZI UNIV, 2023)
This paper tackles the design of a linear controller for autonomous-driving adaptive cruise control systems consisting of platoons of vehicles in a given number. In addition to that, a feed-forward controller is presented in order to improve the performance of the adaptive cruise control system. The mathematical model is obtained for.. vehicles in the longitudinal direction between vehicles, where.. is the number of vehicles in the vehicle convoy. Afterward, the cruise control of the vehicle convoy is performed with the linear-quadratic optimal regulator and the feed-forward controller design. The devised controller has been tested with numerical simulation studies and different velocity trajectory profiles for an eight-vehicle convoy.
Keywords: velocity trajectory profiles eight-vehicle convoy; Linear quadratic regulator; cooperative adaptive cruise control; feed-forward control; autonomous vehicle control systems; STRING STABILITY; STRATEGIES; Engineering